Management of Pancreaticoduodenal Artery Aneurysms Based on a Single-Institution Experience. (October 2021) - Vani, Kunal; Calligaro, Keith D.; Maloni, Krystal; Madden, Nicholas; Troutman, Douglas A.; Dougherty, Matthew J.
Objectives: Pancreaticoduodenal artery aneurysms (PDAAs) are rare and have a high propensity for rupture. Historically, management of PDAAs included surgical reconstruction but has evolved with advances in endovascular therapy. We report our experience with management of PDAAs during the last 30 years. Methods: We retrospectively reviewed our prospectively maintained registry between January 1, 1992 – March 30, 2020. Results: We identified 8 patients with PDAAs: 4 with associated celiac artery occlusive disease and 4 without identifiable etiologies. Four patients were treated with surgical resection of the PDAAs: 2 intact aneurysms underwent concomitant revascularization (superior mesenteric artery-to-hepatic artery Dacron bypass; supra celiac aorta-to-hepatic artery Dacron bypass) and 2 (1 intact, 1 rupture) underwent ligation alone. Four patients were treated with coil embolization of the PDAA: 2 with concomitant stent-graft exclusion of the aneurysm (1 non-rupture, 1 rupture) and 2 without adjunctive measures (intact). There were no deaths nor any significant procedure-related morbidity. Conclusion: Our large single-center experience shows that PDAAs can be successfully treated by open or endovascular intervention with selective revascularization.